Optimalisasi Peran cash waqf linked sukuk Dalam menigkatkan pemberdayaan masyarakat - Muhammad Mahbub Jamalul Lail (Al Iqtishod: Jurnal Pemikiran dan Penelitian Ekonomi Islam, 2022)
This paper is intended to examine and dissect more closely the optimization of the role of Cash Waqf Linked Sukuk as a new idea of the Islamic financial sistem as an effort to empower the community, so that their lives will be more qualified and competitive. The potential and opportunity for cash waqf in Indonesia will be a serious study for the government and waqf stakeholders so that waqf assets can be managed and developed optimally and maximally. The joint work between the government and waqf stakeholders found a new idea, where productive waqf assets would be allocated for investment in SBSN with the CWLS model. The results show that Cash Waqf Linked Sukuk have several very significant roles in increasing community empowerment in various programs and fields, such as health, education, social and economic fields. BWI in utilizing CWLS fees uses several variants of contracts, ijarah, wakalah, qordhul hasan and mudarabah.